Teachers' and Principals' Efforts in Implementing Character Education for Elementary School Students - Nurhikmah Nurhikmah; Arsyad Abdul Gani; Sintayana Muhardini; Candra Candra (STAI Hubbulwathan Duri, 2023)
The efforts of teachers and principals are very important in student character education because the teachers are role models for all students and the principal as management who is able to organize the smooth learning and teaching process. This research uses qualitative methods and descriptive approaches with observation, interview, and documentation tools. The data analysis used using the Miles and Huberman model includes data collection, data reduction, data display, verification, or drawing. The results showed that teachers strive to implement character in students by giving instruction or advice that builds the student's character, developing strategies to implement character building in students, providing good role models for students, approaches to understanding of the student character and innovative approaches use learning methods and media and integrated character development. While principals strive to provide extracurricular and noncurricular programs for students integrated with character education, provide subjects integrated with character education, provide facilities and infrastructure to support character education, direct teachers to provide role models for students, with the community work or parents of students to support the character development of the students.